Pediatric sports injuries - Trentacosta, N. (Pediatric Clinics of North America, 2020)
KEY POINTS - Sports injuries in youth athletics continue to increase with increased sports participation and competitiveness. - Young athletes are susceptible to both acute, traumatic injuries leading to fractures and dislocations as well as chronic overuse injuries. - Lower-extremity injuries are seen more commonly in pediatric and adolescent athletes than those of the upper extremity.